Georgia's Tbilisi Municipal Open Government Issues - Afandi, Syed Agung; Afandi, Muslim; Erdayani, Rizki (Jurnal Ilmu Administrasi Negara (JUAN), 2024)
This study aims to analyze the key issues of Tbilisi open government. Tbilisi plays a major role in open government in Georgia as the only local government selected for the OGP Local Government Pilot Program. Qualitative approaches and bibliometric analysis methods are used in this study. The data used were obtained from the Google Scholar database through Publish or Perish with keywords: Tbilisi information access, Tbilisi transparency, Tbilisi participation, and Tbilisi collaboration. Data selection used Mendeley, while the bibliometric map was obtained from VOSviewer. The findings of this study show that the study of open government in Tbilisi is fluctuating and not very popular. There are 86 relevant articles and 80 topics in the period 2011-2024. The main topics of focus are: challenge, opportunity, education, development, security, energy, policy, reform, civil society, evaluation, partnership, and program. Meanwhile, current and potential topics: technology, smart governance, government maturity, culture, tourism, digital information, public health, green economics, participatory budgeting, budget processes, reporting, standards, inclusiveness, agricultural sector, equality, and gender. Tbilisi is currently focusing on their five open government commitments: Smart Map civic activity portal, participatory budgeting, access to services and civic engagement, transparent governance, and city hall transparency.